Effects of Digital Media on Corporate Reputation in Developing Economies: A Systematic Review - Grace, Adeniji Chinyerem; Olaide, Lewis Anita (Universitas Medan Area, 2025)
The rise of digital media, encompassing social media, email marketing, and review websites, has fundamentally altered how corporate reputation is formed and managed. These platforms are now essential tools, yet they simultaneously introduce new vulnerabilities. This study aims to systematically assess the impact of digital media on corporate reputation by identifying key benefits, persistent challenges, and effective management strategies, addressing a gap by consolidating literature from 2011 to 2024 to provide a cohesive view of the digital reputation landscape. A systematic review was conducted in accordance with PRISMA guidelines, utilizing Google Scholar to include relevant, full-text studies published exclusively between 2011 and 2024. Results show that digital media significantly enhances brand visibility and deepens customer engagement, but this benefit is balanced by considerable risks, primarily the rapid spread of misinformation and negative feedback. Findings highlight that social media is the most influential platform, while email marketing is uniquely effective for building trust through personalized, direct communication. The novelty of this study lies in its synthesis of these varying platform impacts, demonstrating that reputation is now a function of continuous, multi-channel management. Effective digital reputation management demands a multi-faceted approach centered on strategic communication, continuous monitoring, and robust cybersecurity measures. The study strongly recommends that organizations adopt adaptive digital strategies and that regulatory bodies consider stronger governance frameworks. Further research is warranted to explore the impact of emerging technologies on corporate reputation, particularly within developing economies where digital infrastructure and regulatory systems are still evolving.